Persepsi Mahasiswa terhadap Model Pembelajaran Project Based Learning Berbasis Eksperimen dengan Produk Artikel Ilmiah pada Mata Kuliah Botani Tingkat Rendah - Subianto, Fatur Rahman; Turista, Dora Dayu Rahma; Masitah, Masitah; Nasution, Ruqoyyah (Biocaster : Jurnal Kajian Biologi, 2026)
Student perception is their view and assessment of the experience and learning process in the classroom. This is important to study because the success of a learning model is also determined by how students interpret and respond to its implementation. This study aims to determine student perceptions of the implementation of the Project Based Learning (PjBL) learning model based on experiments with scientific articles as products in lower-level botany courses. This study is a quantitative descriptive study with an ex post facto approach using a survey method. Sampling was carried out using a purposive sampling technique on students of the Biology Education Study Program, Faculty of Teacher Training and Education, Mulawarman University. The data analysis technique used descriptive statistical analysis. The results of the data analysis show that the average result of all observed aspects obtained a percentage value of 84.99% which is included in the "very good" category, so it can be concluded that students of the Biology Education Study Program have a positive perception of the implementation of the Project Based Learning (PjBL) learning model based on experiments with scientific articles as products in lower-level botany courses. Therefore, these findings emphasize that the implementation of this learning model is worthy of being maintained and further developed with improvements, particularly in technical aspects and structured academic mentoring to optimize the quality of the learning process and outcomes.